2022
DOI: 10.1128/jcm.01769-21
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Two High-Throughput 16S rRNA Gene Sequencing Workflows for Taxonomic Assignment of Unidentifiable Bacterial Pathogens in Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Bacterial pathogens that cannot be identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) are occasionally encountered in clinical laboratories. The 16S rRNA gene is often used for sequence-based analysis to identify these bacterial species. Nevertheless, traditional Sanger sequencing is laborious, time-consuming and low-throughput. Here, we compared two commercially available 16S rRNA gene sequencing tests, which are based on Illumina and Nanopore sequenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The long-read Nanopore sequencing is advantageous for sequencing the entire 16S rRNA gene, which allows better taxonomic resolution at the species level. A previous study conducted by our group demonstrated that Nanopore sequencing achieved a diagnostic accuracy of 96.36%, which was similar to that of Sanger sequencing, for bacterial identification using 16S rRNA gene sequencing in clinical isolates (Lao et al, 2022). Due to its high sensitivity, real-time analysis platform, and the ability to identify mixed species, Nanopore 16S rRNA gene sequencing (Nanopore 16S) of direct specimens could be a potential alternative for rapid bacterial identification in clinical laboratories.…”
Section: Introductionmentioning
confidence: 64%
“…The long-read Nanopore sequencing is advantageous for sequencing the entire 16S rRNA gene, which allows better taxonomic resolution at the species level. A previous study conducted by our group demonstrated that Nanopore sequencing achieved a diagnostic accuracy of 96.36%, which was similar to that of Sanger sequencing, for bacterial identification using 16S rRNA gene sequencing in clinical isolates (Lao et al, 2022). Due to its high sensitivity, real-time analysis platform, and the ability to identify mixed species, Nanopore 16S rRNA gene sequencing (Nanopore 16S) of direct specimens could be a potential alternative for rapid bacterial identification in clinical laboratories.…”
Section: Introductionmentioning
confidence: 64%
“…The full-length 16S sequencing workflow based on Oxford Nanopore Technology has the advantage of greater efficiency in species classification 15 . This strategy is also cost-effective 16 due to the cheaper reusable flow cells, more flexible input sample requirement and a rapid turnaround time 17 . At present, we investigate the alteration of the gut microbiome in wild-borne macaques that were translocated and housed in a hygienic facility for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…The time taken by Illumina sequencing was 78 h, whereas nanopore sequencing required 8.25 h. Furthermore, the study found that although Illumina sequencing had high accuracy in base recognition, nanopore sequencing provided a higher taxonomic resolution at the species level. Therefore, compared with MALDI-TOF MS and Illumina sequencing, nanopore sequencing technology has a higher species identification ability, despite its higher sequencing error rate [ 75 ].…”
Section: Application Of Nanopore Sequencing In the Identification Of ...mentioning
confidence: 99%